1996
DOI: 10.1007/bf00311984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endogenous hypergastrinemia on carcinogenesis in the rat esophagus

Abstract: We surgically prepared a hypergastrinemia model in rats and studied the effects of hypergastrinemia on chemically induced carcinogenesis in the esophagus. Operations were performed on 5-week-old male Donryu rats as follows: (1) truncal vagotomy plus pyloroplasty (group V), (2) segmental gastrectomy plus pyloroplasty (group G), (3) antrectomy (group A), and (4) no operation (group C) as a control. From the age of 6 weeks, the animals were given 0.003% N-methyl- N-amylnitrosamine (MAN) solution as drinking water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Given the finding of potential roles of gastrin precursors in stimulating human cancer growth in vitro [25,43,44] and animal cancer models in vivo [26, 28, It is well known that the effect of amidated gastrin on stimulating gastrointestinal cancer cell growth was mediated by gastrin/CCK2 receptors [15,17,18], a gastringastrin/CCK2 receptor loop was found in some human cancers [15,16,20,24] and targeting of gastrin/CCK2 receptor by peptide or antibody exhibited a therapeutic potential in colonic, pancreatic and hepatocellular carcinoma cell lines in vitro [46]. In animals, gastrin has been found to stimulate normal esophageal epithelium proliferation [31,47,48] and promote carcinogenesis [32]. In Barett's esophagus, gastrin induces proliferation [33], metaplasia [33], and reduced apoptosis [21], which were mediated by upregulated gastrin/CCK2 receptors [21,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the finding of potential roles of gastrin precursors in stimulating human cancer growth in vitro [25,43,44] and animal cancer models in vivo [26, 28, It is well known that the effect of amidated gastrin on stimulating gastrointestinal cancer cell growth was mediated by gastrin/CCK2 receptors [15,17,18], a gastringastrin/CCK2 receptor loop was found in some human cancers [15,16,20,24] and targeting of gastrin/CCK2 receptor by peptide or antibody exhibited a therapeutic potential in colonic, pancreatic and hepatocellular carcinoma cell lines in vitro [46]. In animals, gastrin has been found to stimulate normal esophageal epithelium proliferation [31,47,48] and promote carcinogenesis [32]. In Barett's esophagus, gastrin induces proliferation [33], metaplasia [33], and reduced apoptosis [21], which were mediated by upregulated gastrin/CCK2 receptors [21,33].…”
Section: Discussionmentioning
confidence: 99%
“…Karaki et al [32] reported that hypergastrinemia in rats enhances chemical carcinogen induced esophageal carcinoma. In human, the important role of long-term hypergastrinemia on increasing risk of esophageal cancer has been reported to be mediated by stimulating the growth of Barrett's esophageal epithelium that were via several mechanisms including the activation of the gastrin/CCK2 receptor [30,33] and/or reduction of apoptosis [21].…”
Section: Introductionmentioning
confidence: 98%
“…A recent study by Karakai et al . showed that squamous cell carcinomas grow more rapidly under the influence of high levels of gastrin, but that there was no differentiation to the adenocarcinomas 78 . Jankowski et al .…”
Section: Discussionmentioning
confidence: 99%
“…Iron supplementation, 52 endogenous hypergastrinemia, 53 alcohol, N ‐nitrosononicotine (NNN), 54 and zinc deficiency act as promoters of esophageal carcinogenesis in the N ‐nitrosamine rat and mouse model 55–57 . Ethanol promotes carcinogenesis through excessive cell proliferation induced by disordered lipid and eicosanoid metabolism 58 …”
Section: Carcinogenesis Animal Models and Therapeutic Interventionsmentioning
confidence: 99%
“…51 It appears that pancreatic juice is the most potent component of the duodenal refluxate in the promotion of esophageal carcinogenesis in rats. 51 Iron supplementation, 52 endogenous hypergastrinemia, 53 alcohol, N-nitrosononicotine (NNN), 54 and zinc deficiency act as promoters of esophageal carcinogenesis in the N-nitrosamine rat and mouse model. [55][56][57] Ethanol promotes carcinogenesis through excessive cell proliferation induced by disordered lipid and eicosanoid metabolism.…”
Section: Carcinogenesis Animal Models and Therapeutic Interventionsmentioning
confidence: 99%